A novel strategy of inducing solar absorption and accelerating heat release for cooling asphalt pavement. (1st January 2018) - Yinfei, Du; Zheng, Han; Jiaqi, Chen; Weizheng, Liu
Highlights: Steel rods were implanted in asphalt layers to construct thermal channels. Approximately 30.6% more solar heat was induced to be absorbed by asphalt pavement. The heat in pavement was induced to fast transfer to the base layer through steel rods. The surface and inner temperatures reduced by maximums of 3.5 °C and 6.4 °C, respectively. The maximum rutting depth decreased by 49.2%. Abstract: High-temperature asphalt pavements contribute to the development of urban heat island, rutting distress and asphalt aging, etc. Implanting steel rods in the middle and bottom asphalt layers was proved to be able to construct thermal channels, but it was difficult to reduce surface and inner temperatures simultaneously. To increase solar absorption and accelerate heat release in asphalt pavement, a novel strategy of oriented heat induction was proposed according to the effect of rod-implanting mode on temperature profile. The simulation results show that the proposed structure absorbed 30.6% solar heat more than control structure. The implanting of steel rods changed the heat flow characteristics as well. The heat in the asphalt mixture in the top layer was absorbed by steel rods, which was then released to the asphalt mixture in the bottom layer after a period of fast downward heat transfer. The surface and inner temperatures reduced by maximums of 3.5 °C and 6.4 °C, respectively, compared to the control structure. The temperature reduction was verified by an indoor irradiation test. As a result, the maximum rutting depth of the proposed structure decreased by 49.2%. The proposed strategy of heat induction is expected to be used to cool asphalt pavement by inducing solar absorption and accelerating heat release.